2015
DOI: 10.1002/pssa.201532506
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Mg‐implanted GaN p–i–n diode

Abstract: An Mg‐implanted p–i–n diode was fabricated and characterized. Mg activation was achieved using the multicycle rapid thermal annealing technique with rapid heating pulses up to 1340 °C. The surface of the implanted GaN after annealing was smooth (0.94 nm RMS roughness) with growth steps evident as characterized by atomic force microscopy. The full width at half‐maximum of the implanted GaN E2 Raman mode approaches that of the as‐grown GaN after the annealing process, indicating that the annealing process is abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…Although techniques for activating implanted acceptors seem to not be mature, successful fabrication of the devices has started to appear recently. Greenlee et al reported the fabrication of a p‐i‐n diode by Mg implantation. The annealing process used in their experiment was a multi‐step annealing involving annealing at 1000 °C at 24 bar overpressures of N 2 and rapid thermal heating done 20 times at 1340 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Although techniques for activating implanted acceptors seem to not be mature, successful fabrication of the devices has started to appear recently. Greenlee et al reported the fabrication of a p‐i‐n diode by Mg implantation. The annealing process used in their experiment was a multi‐step annealing involving annealing at 1000 °C at 24 bar overpressures of N 2 and rapid thermal heating done 20 times at 1340 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of implanted Mg is difficult . In the fabrication of p ‐type GaN using ion implantation, nitrogen vacancies ( V N ) are expected to act as shallow compensating centers .…”
Section: Introductionmentioning
confidence: 99%
“…The activation of implanted Mg is difficult. [10][11][12][13][14][15][16][17][18] In the fabrication of p-type GaN using ion implantation, nitrogen vacancies (V N ) are expected to act as shallow compensating centers. [19] However, since a variety of defects are introduced during ion implantation, the study of interactions between irradiation-induced defects, such as vacancy complexes between Ga vacancies (V Ga ) and V N , is important to effectively utilize ion implantation for GaN devices.…”
Section: Introductionmentioning
confidence: 99%
“…The high defect density in GaN grown on a sapphire substrate might have been a reason for the unsuccessful formation of a p-type region. Very recently, the successful formation of p-type regions on GaN epitaxial layers on free-standing GaN substrates by Mg ion implantation has been confirmed by observing the rectifying characteristics of p-n junctions formed by applying multicycle rapid thermal annealing, 5,6 standard high-temperature annealing, 7,8 and coimplantation of the N-face of GaN with Mg and H ions. 9 However, it has been reported that defects remain in the Mg-implanted GaN layer even after high-temperature annealing on the basis of positron annihilation spectroscopy (PAS) and photoluminescence (PL) studies.…”
mentioning
confidence: 95%